Bank Health Analysis Using the Camel Method at PT. Bank Syariah Indonesia Tbk 2022-2024 - Syafira Enggar Khoirul Nisa; Sri Murwanti (STIE Amkop Makassar, 2026)
This research endeavors to examine the soundness level of PT Bank Syariah Indonesia Tbk during the time frame of 2022–2024 utilizing the CAMEL framework, which encompasses Capital, Asset Quality, Management, Earnings, and Liquidity. The study adopts a quantitative descriptive methodology, employing secondary data procured from the annual financial statements disseminated by PT Bank Syariah Indonesia Tbk and the Indonesia Stock Exchange. The analytical process involves the computation of essential financial ratios, such as the Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Net Profit Margin (NPM), Operating Expenses to Operating Income (BOPO), and Financing to Deposit Ratio (FDR), subsequently followed by trend analysis and juxtaposition with the soundness benchmarks delineated by Bank Indonesia. The findings reveal that PT Bank Syariah Indonesia Tbk consistently sustained a condition classified as healthy to very healthy throughout the duration of the study. The CAR ratio consistently surpassed the regulatory minimum, signifying robust capital adequacy. Asset quality exhibited a progressive enhancement, as evidenced by a persistent reduction in the NPF ratio. The performance of management and profitability demonstrated favorable trajectories, as indicated by the rising NPM and declining BOPO ratios, which denote improved operational efficiency. Regarding liquidity, the FDR ratio remained within acceptable thresholds, reflecting effective intermediation while preserving liquidity stability. In summary, the results indicate that PT Bank Syariah Indonesia Tbk showcased stable financial performance and reinforced soundness across all CAMEL dimensions throughout the period of 2022–2024.